Genetic Diversity and Pathogenicity of Ralstonia solanacearum Causing Tobacco Bacterial Wilt in China - Li, Yanyan (Plant disease, 2016)
Bacterial wilt caused by Ralstonia solanacearum is the most serious soilborne disease of tobacco (Nicotiana tabacum) in China. In this study, 89 strains were collected in 2012 to 2014 from across the four major tobacco-growing areas in China. The strains were identified as phylotype I by multiplex polymerase chain reaction and further divided into seven sequevars based on polymorphisms in the endoglucanase (egl) gene. Among the seven sequevars, four (15, 17, 34, and 44) have been previously described as pathogens of tobacco and two (13 and 14), which are reported here on tobacco, were previously found only on other plants. In addition, a new sequevar named 54 was identified. Strains from tobacco from different regions showed different levels of genetic diversity based on partial egl gene sequences. The farther north the distribution, the lower the gene diversity found. Pathogenicity of 27 representative strains was assessed by inoculation onto three tobacco cultivars of varying susceptibility. Through cluster analysis of area under the disease progress curve values, the 27 strains were classified into different pathotypes based on virulence; however, no obvious associations were found between sequevar and pathotype. These results will assist in determining geographical distribution of strains, and provide the foundation for breeding and integrated management programs in China